2018
DOI: 10.1193/111417eqs236mr
|View full text |Cite
|
Sign up to set email alerts
|

Surface Faulting Caused by the 2016 Central Italy Seismic Sequence: Field Mapping and LiDAR/UAV Imaging

Abstract: The three mainshock events (M6.1 24 August, M5.9 26 October, and M6.5 30 October 2016) in the Central Italy earthquake sequence produced surface ruptures on known segments of the Mt. Vettore–Mt. Bove normal fault system. As a result, teams from Italian national research institutions and universities, working collaboratively with the U.S. Geotechnical Extreme Events Reconnaissance Association (GEER), were mobilized to collect perishable data. Our reconnaissance approach included field mapping and advanced imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…A high‐angle transverse dislocation does not contribute to improving the fit to the data (Figures S9–S11). Sections on the relocated seismicity made across the supposed oblique structure (see Figure 3 of Chiaraluce et al, ) should have shown subhorizontal clusters of aftershocks at increasing depths going from the OAST trace toward NW, that is, supposedly enlightening the oblique structure; instead, these sections do not show any clear evidence of this. Depending on its actual downdip dimension and fault dip angle, an oblique dislocation would also cut the Norcia normal fault system, located some 10 km west of the MVB fault system and which represents another major seismogenic structure of the Central Apennines (Galli et al, ). As no geological and geophysical information on the geometry, on the extent at depth, on the dip and strike angles of this supposed cross‐structure is available, the deep geometry of the OAST cannot be extrapolated by only considering its surface geometric characteristics (i.e., by simply prolonging downward the low‐angle plane at the surface). We did not find any long‐term geological and morphotectonic evidence of the presence of an oblique fault in the southern part of the Castelluccio plain, nor evidence of surface rupture associated with it has been surveyed (Galadini et al, ; Civico et al, ; Gori et al, ; Villani, Civico, et al, ). Even if transverse high‐angle synthetic normal faults that would connect at depth to the supposed low‐angle transverse fault have been hypothesized (Scognamiglio et al, ; Walters et al, ), no evidence of these are present in the field, and they are not necessary to reconcile the geological setting of the southern portion of the Castelluccio plain (Figure , geological cross sections, and Figure S2f).…”
Section: Discussionmentioning
confidence: 77%
“…A high‐angle transverse dislocation does not contribute to improving the fit to the data (Figures S9–S11). Sections on the relocated seismicity made across the supposed oblique structure (see Figure 3 of Chiaraluce et al, ) should have shown subhorizontal clusters of aftershocks at increasing depths going from the OAST trace toward NW, that is, supposedly enlightening the oblique structure; instead, these sections do not show any clear evidence of this. Depending on its actual downdip dimension and fault dip angle, an oblique dislocation would also cut the Norcia normal fault system, located some 10 km west of the MVB fault system and which represents another major seismogenic structure of the Central Apennines (Galli et al, ). As no geological and geophysical information on the geometry, on the extent at depth, on the dip and strike angles of this supposed cross‐structure is available, the deep geometry of the OAST cannot be extrapolated by only considering its surface geometric characteristics (i.e., by simply prolonging downward the low‐angle plane at the surface). We did not find any long‐term geological and morphotectonic evidence of the presence of an oblique fault in the southern part of the Castelluccio plain, nor evidence of surface rupture associated with it has been surveyed (Galadini et al, ; Civico et al, ; Gori et al, ; Villani, Civico, et al, ). Even if transverse high‐angle synthetic normal faults that would connect at depth to the supposed low‐angle transverse fault have been hypothesized (Scognamiglio et al, ; Walters et al, ), no evidence of these are present in the field, and they are not necessary to reconcile the geological setting of the southern portion of the Castelluccio plain (Figure , geological cross sections, and Figure S2f).…”
Section: Discussionmentioning
confidence: 77%
“…This swarm of moderate-size events is part of the 2016-2017 central Italy seismic sequence that affected the central Apennines starting on 24 August 2016 with a M W 6.0 event in the Amatrice area ( Figure 1), and then culminated with the 30 October 2016 M W 6.5 largest event [11]. The geodetic, seismological, and geological studies published so far (e.g., [11][12][13][14][15][16][17][18][19][20]) agree in attributing the bulk of the 2016-2017 central Italy seismic sequence to the progressive rupture of different segments of two main NW-SE striking extensional structures of the central Apennines, the Laga Mts., and Mt. Vettore-Mt.…”
Section: Introductionmentioning
confidence: 91%
“…Several authors studied the causes/effects of the 2016 earthquakes from many points of view, as structural-geology, geophysics, seismology, paleoseismology, geomorphology, interferometry, geodesy, hydrogeology, engineering [15,31,32,[34][35][36]39,40,, but only a few authors have provided and elaborated data acquired through drones [92][93][94][95]. In addition, there are no author-produced image analyses of coseismic ruptures employing the techniques we propose here.…”
Section: Discussionmentioning
confidence: 99%